2020
DOI: 10.1093/rheumatology/keaa298
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and radiographic comparison of patients with psoriatic arthritis from different ethnic backgrounds

Abstract: Objectives There are few papers concerning ethnic differences in disease expression in PsA, which may be influenced by a number of genetic, lifestyle and cultural factors. This article aims to compare clinical and radiographic phenotypes in people of South Asian (SA) and North European (NE) origin with a diagnosis of PsA. Methods This was a cross-sectional observational study recruiting patients of SA and NE origin from two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In contrast, Giant cell arteritis (GCA) is much less common (risk reduced to about a quarter) in patients of South Asian descent [20,21]. In psoriatic arthritis, South Asian ethnicity appears to be associated with worse clinical phenotype and worse patient outcomes [22]. Ankylosing spondylitis and axial spondyloarthritis are more common in White patients and associated with higher rates of HLA B27 positivity compared to Blacks, but Blacks have increased severity and worse functional outcomes [23].…”
mentioning
confidence: 99%
“…In contrast, Giant cell arteritis (GCA) is much less common (risk reduced to about a quarter) in patients of South Asian descent [20,21]. In psoriatic arthritis, South Asian ethnicity appears to be associated with worse clinical phenotype and worse patient outcomes [22]. Ankylosing spondylitis and axial spondyloarthritis are more common in White patients and associated with higher rates of HLA B27 positivity compared to Blacks, but Blacks have increased severity and worse functional outcomes [23].…”
mentioning
confidence: 99%
“…The extent to which epidemiological differences can be explained by under-diagnosis among patients with darker skin tones and in populations where there is inequity in access to healthcare is poorly understood. Limited studies into disease phenotype have suggested that non-white patients may have a more severe phenotype, which may well be multifactorial 9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…For example; lower prevalence has been reported in Asian countries like Japan and China (0.1 in 100,000, and 2 in 100,000 respectively) [18]; PsA in Korea had predominant spinal involvement; Chinese may have a milder course in relation to impact on physical function; and Indians with psoriasis had twice the risk of developing PsA compared with Chinese [16,19]. Compared with Chinese, Malay and European populations, ethnic South Asians may have greater disease activity and experience poorer physical function [15][16][17]20]. This nding was also observed in South Asians living in both Western and Asian countries, suggesting a stronger in uence from genetic rather than geographic factors [21].…”
Section: Introductionmentioning
confidence: 99%